Environmental Health Risk Assessment in Tabing Banda Gadang Subdistrict, Padang City - Fitra, Miladil; Desman, Akhirul; Hidayanti, Rahmi (Baiman Bauntung Batuah Center, 2024)
Sanitation problems in Indonesia still involve deviant social behavior, namely defecation habits anywhere. According to World Health Organization, around 2.5 billion people worldwide do not have access to proper sanitation facilities. Indonesia itself is ranked second after India, with a high number of people still defecating in the open; this is due to people's habits, which are very difficult to change because they have been inherited. The use of surface water sources, namely river water, with physical water quality that does not meet requirements, the absence of facilities for wastewater disposal, and the absence of household waste management can cause health hazards to the environment. The research aims to know the risky health environment in the sub-district Tabing Banda Gadang, Padang City. Study method This Quantitative nature descriptive analytic with approach Studies Evaluation Risk Health Environment is a participatory study to understand the condition of sanitation and hygiene facilities and community behaviors at the household scale, the results of data processing and analysis that can describe the determination of risk areas from each region to the village/sub-district level. The results of the study found that the risk areas were Water Sources with results of Not enough risk (value 28), Domestic Wastewater with Medium risk (value 68), Medium Risk Waste (value 51), high risk of waterlogging (value 58) and Clean and Healthy Living Behavior is not enough risky (value 32) it can be concluded that the sanitation risk index of Tabing Banda Gadang Village is included in the Current Risk with a value of 237. Tabing Banda Gadang Village is at high risk of waterlogging, so it is recommended that the Village facilitate the construction of drainage by coordinating with the Department of Housing and Public Works to resolve the waterlogging problem.